2012
DOI: 10.1007/s00464-012-2254-z
|View full text |Cite
|
Sign up to set email alerts
|

Low impact of staging EUS for determining surgical resectability in esophageal cancer

Abstract: Background Although studies have shown that EUS has a high sensitivity and specificity for T and N staging, the value of EUS for staging tumors as resectable or nonresectable after CT of the chest and abdomen and US neck assessment, is largely unknown. This study was designed to assess the diagnostic value of EUS for determining resectability of esophageal cancer. Methods A retrospective analysis of all consecutive patients with esophageal carcinoma who underwent staging EUS, CT, and US. Tumors were considered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…Computed tomography (CT) has been widely used to identify the location of a cancer, relationship to surrounding organs, and to assess the distant metastasis; however, it cannot depict the specific layer invasion of the esophageal wall due to its poor soft‐tissue resolution . Endoscopic ultrasonography (EUS) can be used to depict the esophageal layers but is restricted by high operator dependency, issues that result from the pathologically stenotic esophageal wall, and its semiinvasive nature . Thus, a more precise and convenient imaging modality is needed to evaluate the esophageal wall invasion by carcinomas.…”
mentioning
confidence: 99%
“…Computed tomography (CT) has been widely used to identify the location of a cancer, relationship to surrounding organs, and to assess the distant metastasis; however, it cannot depict the specific layer invasion of the esophageal wall due to its poor soft‐tissue resolution . Endoscopic ultrasonography (EUS) can be used to depict the esophageal layers but is restricted by high operator dependency, issues that result from the pathologically stenotic esophageal wall, and its semiinvasive nature . Thus, a more precise and convenient imaging modality is needed to evaluate the esophageal wall invasion by carcinomas.…”
mentioning
confidence: 99%
“…Two studies determined the influence of EUS after CT-alone, with a questionnaire, and found that EUS changed the treatment decision in 24–34% of the patients 4,6. A study by Van Zoonen determined that although EUS increased the specificity after CT and ultrasound of the neck, the additional value on determining the surgical resectability was limited 16. Moreover, Findlay et al found that the risk of EUS in T2-4a patients on CT outweighed the additional information of EUS on T- and N-stage 5.…”
Section: Discussionmentioning
confidence: 99%
“…In future studies with focus on neoadjuvantly treated EC patients, the role of GTn as potential predictor of response may be evaluated. However, considering the fact that present available imaging tools are insufficient to avoid over‐ and undertreatment of the patients because of incorrect disease staging GTn may represent a marker to help therapy decision making .…”
Section: Discussionmentioning
confidence: 99%